2014
DOI: 10.1016/j.bmcl.2013.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening reveals allosteric inhibitors of the Toxoplasma gondii thymidylate synthase–dihydrofolate reductase

Abstract: The parasite Toxoplasma gondii can lead to toxoplasmosis in those who are immunocompromised. To combat the infection, the enzyme responsible for nucleotide synthesis thymidylate synthase-dihydrofolate reductase (TS-DHFR) is a suitable drug target. We have used virtual screening to determine novel allosteric inhibitors at the interface between the two TS domains. Selected compounds from virtual screening inhibited TS activity. Thus, these results show that allosteric inhibition by small drug-like molecules can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The ligands were prepared using Maestro’s Ligprep utility, and Epik software 37 was used to generate protonation states at the target pH (7.0 ± 2.0). 38 The protein structure of IGPS was obtained from the Protein Data Bank (PDB entry 1GPW), the crystal structure of the enzyme complex from T. maritima . The position of PRFAR in the HisF active site was determined after superimposing the phosphate groups in the T. maritima IGPS crystal and the PRFAR-bound complex in the yeast enzyme (PDB entry 1OX5).…”
Section: Methodsmentioning
confidence: 99%
“…The ligands were prepared using Maestro’s Ligprep utility, and Epik software 37 was used to generate protonation states at the target pH (7.0 ± 2.0). 38 The protein structure of IGPS was obtained from the Protein Data Bank (PDB entry 1GPW), the crystal structure of the enzyme complex from T. maritima . The position of PRFAR in the HisF active site was determined after superimposing the phosphate groups in the T. maritima IGPS crystal and the PRFAR-bound complex in the yeast enzyme (PDB entry 1OX5).…”
Section: Methodsmentioning
confidence: 99%
“…These compounds include glutaric acid (2), N-(4-carboxyphenyl) succinamic acid (3), diglycolic anhydride (4), (R)-4-((1-cyclopropylethyl) (phenyl)amino)-4-oxobutanoic acid, (E)-4-((2-(methoxycarbonyl)-4-methythiophen-3-yl)amino)-4-oxobut-2-enoic acid, and 3,4-dihydro-2H-benzo [b][ 1 , 4 ]dioxepine-7-carboxylic acid, in addition to the previously reported diphosphonate PDPA referred to, in the current study, by compound (1) [ 13 , 21 ]. Previous studies on PDPA reported that its binding to hTS was able to cause significant inhibition of its activity, and stabilize loop 181–197 in an inactive conformation [ 22 , 23 ]. In the present investigation, PDPA exhibited higher selectivity for inhibition of native hTS relative to active-stabilized R163K-hTS.…”
Section: Discussionmentioning
confidence: 99%
“…Cheminformaticsbased virtual screens are being performed to identify novel antiToxoplasma compounds (87,124,125). The availability of crystal structures for some of the T. gondii proteins and the improvement in computational molecular modeling approaches facilitate this approach.…”
Section: Compounds Identified In Screensmentioning
confidence: 99%